Potential Utility of Natural Products against Oxidative Stress in Animal Models of Multiple Sclerosis - Zheng Zha; Sisi Liu; Yijiang Liu; Chen Li; Lei Wang (Antioxidants, 2022)
Multiple sclerosis (MS) is an autoimmune-mediated degenerative disease of the central nervous system (CNS) characterized by immune cell infiltration, demyelination and axonal injury. Oxidative stress-induced inflammatory response, especially the destructive effect of immune cell-derived free radicals on neurons and oligodendrocytes, is crucial in the onset and progression of MS. Therefore, targeting oxidative stress-related processes may be a promising preventive and therapeutic strategy for MS. Animal models, especially rodent models, can be used to explore the in vivo molecular mechanisms of MS considering their similarity to the pathological processes and clinical signs of MS in humans and the significant oxidative damage observed within their CNS. Consequently, these models have been used widely in pre-clinical studies of oxidative stress in MS. To date, many natural products have been shown to exert antioxidant effects to attenuate the CNS damage in animal models of MS. This review summarized several common rodent models of MS and their association with oxidative stress. In addition, this review provides a comprehensive and concise overview of previously reported natural antioxidant products in inhibiting the progression of MS.